Prophylactic oral nystatin for preterm babies under 33 weeks' gestation decreases fungal colonisation and invasive fungaemia. Issue 4 (26th November 2008) - Ganesan, K; Harigopal, S; Neal, T; Yoxall, C W
Abstract : Background: Invasive fungal infection is an important cause of mortality and morbidity in extremely preterm babies. Colonisation with Candida is a risk factor for systemic infection. A policy of oral nystatin prophylaxis was introduced in November 2000 with the aim of reducing the incidence of invasive fungaemia. Aim: To determine whether this policy had reduced the rates of fungal colonisation and invasive fungal infection. Methods: All neonates of <33 weeks' gestation born between 1998 and 2003 were studied. Neonates born between January 1998 and October 2000 who did not receive nystatin prophylaxis (group A) were compared with those born between November 2000 and December 2003 who received nystatin prophylaxis (group B). Infant details, blood culture results and the results of weekly surface swabs were recorded. Results: 1459 neonates (group A = 724, group B = 735) of <33 weeks' gestation were admitted in the study period. There were no differences in birth weight, gestation, gender or proportion of babies transferred in from other units between the groups. There was a reduction in colonisation from 257 (35.5%) in group A to 132 (18%) in group B. The incidence of invasive fungaemia decreased from 30 (4.1%) to 13 (1.8%) between the two groups. There was also a reduction in mortality between the two groups from 17.8% to 11.8%. Conclusions: The introduction of a prophylactic nystatin administration policy for babies born before 33 weeks was associated with a significant reduction in fungal colonisation and invasive fungal infection.